2019
DOI: 10.3390/ma12223785
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Forming Process and Deformation Behavior of Inner Ring in the Wheel Hub Bearing Based on Riveting Assembly

Abstract: The orbital riveting process has been successively adopted in the assembly of wheel hub bearing, due to its special merits of high efficiency, low cost, and so on. The forming process and deformation behavior of the inner ring have significant influence on the axial clamping force and bearing clearance, however, which haven’t been addressed yet. In this study, a numerical simulation platform for the assembly of the hub bearing is established by the joint use of the static implicit and dynamic explicit algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Cavity prediction is thus important. The DPTR WBU in Figure 1 was manufactured using a process that differs greatly from the process used in the case of mechanically separable bearing [26,29]; DPTR WBU manufacture requires preloading of the inner races and careful control of the forming load. The inner DPTR races exhibit high-level elastic deformation and stresses that become concentrated at weak points (Figure 1).…”
Section: Dptr Wbu Assembling Process and Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavity prediction is thus important. The DPTR WBU in Figure 1 was manufactured using a process that differs greatly from the process used in the case of mechanically separable bearing [26,29]; DPTR WBU manufacture requires preloading of the inner races and careful control of the forming load. The inner DPTR races exhibit high-level elastic deformation and stresses that become concentrated at weak points (Figure 1).…”
Section: Dptr Wbu Assembling Process and Analysis Modelmentioning
confidence: 99%
“…Xiong et al [29] employed implicit and explicit FEMs with hexahedral FEs to assemble a WBU. They showed an acceptable agreement between the predictions and the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The variables influencing this development are, for example: an increase in engine power, weight, an advanced production process, simplification of assembly, up to new materials. But also the deformation behavior of the inner ring, because the deformation of the inner ring has a direct effect on the bearing play and the clamping force [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Milutinovic et al [20] analyzed and compared mechanical properties of a nonaxisymmetric steel U-cross joint component manufactured by cold orbital forging and conventional hot forging and found that the component formed by orbital forging showed better mechanical properties than the component manufactured by conventional forging. Also, cold orbital forging can be utilized for riveting assembly, such as the assembly of wheel hub bearing [21,22] and artificial joints production [23]. Recently, a novel orbital forming process called ultrasonic orbital microforming (UOM) was developed to form metal components whose dimensions were smaller than 1 mm [24,25].…”
Section: Introductionmentioning
confidence: 99%